Embodying Yahguudang : respectful relations between Indigenous and settler people(s) on Haida Gwaii - Fung, Stephanie See-Pui (2021)
Indigenous–non-Indigenous relations have been fraught with ignorance, misunderstandings, and racism since the imposition of Settler colonialism on Turtle Island. Our current era is characterized by change, and as tensions continue to rise over title to the lands and waters of this continent, there is a growing need and desire to work towards more just and respectful relations between Indigenous and Settler People(s). I use a phenomenological approach to explore Settler experiences of respectful relations with Haida People, drawing on in-depth, one-on-one interviews with long-term Settlers to Haida Gwaii. Interview transcripts were analyzed drawing on theoretical concepts including the “ethical space of engagement” (Ermine, 2007), Barker and Lowman’s (2015) “space of dangerous freedom”, and Regan’s (2010) notion of “unsettling the settler within” revealing that respectful relations are understood to be embodying yahguudang, the Haida principle of respect. The findings reveal that Settlers strive towards this in an ongoing process of becoming following four crucial pathways: embodied humility, embodied acknowledgment, embodied responsibility, and a sense of embodied reciprocity. The current Haida Gwaii context offers unique opportunities for Settlers to learn and practice embodying these ways of being and also of becoming, which create potential for building genuine and lasting respectful relations with Haida People. Participant experiences, along with the socio-political circumstances that surround their experiences, may offer insight for other Settlers wishing to live in respectful relations with Indigenous People(s) across Turtle Island. Keywords: Indigenous–Settler relations, yahguudang, embodied respect, Ethical Space of Engagement, Haida Gwaii, phenomenology, settler colonialism, decolonization, reconciliation